2000
DOI: 10.1016/s0169-7722(00)00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated transport of a PAH mixture by a rhamnolipid biosurfactant in porous silica matrices

Abstract: Ž. The facilitated transport of a mixture of three polycyclic aromatic hydrocarbons PAH Ž . naphthalene, fluorene, and phenanthrene by a rhamnolipid biosurfactant was determined with silica, octadecyl-coated silica, and humic acid-coated silica columns. The retardation factors for Ž . the contaminants in the absence of rhamnolipid ranged from 1.8 naphthalene with silica to 708 Ž . phenanthrene with octadecyl-coated silica . The retardation factors for phenanthrene were up to eightfold lower in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The biosurfactant did not facilitate just one of the two steps in equation 1 and leave the other unaffected, since a good fit could not be obtained when using the values for k 1 and k Ϫ1 or for k 2 and k Ϫ2 from the experiment without rhamnolipid and accounting for solubilization of NPN by rhamnolipid by using rhamnolipid-water partitioning constants for NPN that were estimated from a linear free-energy relationship (27). Thus, it may be that the uptake process in the presence of rhamnolipid becomes more complex than suggested by equation 1, e.g., due to the direct uptake of NPN solubilized by rhamnolipid.…”
Section: Resultsmentioning
confidence: 99%
“…The biosurfactant did not facilitate just one of the two steps in equation 1 and leave the other unaffected, since a good fit could not be obtained when using the values for k 1 and k Ϫ1 or for k 2 and k Ϫ2 from the experiment without rhamnolipid and accounting for solubilization of NPN by rhamnolipid by using rhamnolipid-water partitioning constants for NPN that were estimated from a linear free-energy relationship (27). Thus, it may be that the uptake process in the presence of rhamnolipid becomes more complex than suggested by equation 1, e.g., due to the direct uptake of NPN solubilized by rhamnolipid.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of HOCs from soil matrix in presence of surfactants is a complex process, since the surfactants first remove the HOCs from the soil and at the same time surfactants are also adsorbed on the soil surfaces and change the surface characteristic, as a result, some times HOCs are readsorbed on the soil surface. Due to the complex nature of the process many researchers have studied on removal efficiency of the organic compounds from the soil matrix using different surfactants like single synthetic [28,95,105,[257][258][259][260][261][262][263][264], mixture of synthetic [105,261,264,265], and biosurfactants [28,193,[266][267][268] to improve the basic understanding.…”
Section: Surfactant Enhanced Hocs Removalmentioning
confidence: 99%
“…Zhang et al (1997) reported that solubilization of phenanthrene in absence of biosurfactant was 0.69 mg/l whereas in the presence of purified rhamnolipids from P. aeruginosa ATCC 9027 (0.30-0.35 mmol/l) the solubilization of phenanthrene increased up to 35 mg/l. Study by Noordman et al (2000) reported that rhamnolipids concentration below its CMC did not display solubilization activity for PAHs.…”
Section: Introductionmentioning
confidence: 97%